Pengaruh Disiplin Kerja Dan Pelatihan Terhadap Kinerja Karyawan Dengan Budaya Organisasi Sebagai Variabel Moderasi Pada Rumah Sakit Milik Pemerintah di Kota Medan - Willy Yusnandar; Roydi Nefri; Safi'i Siregar (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
This study aims to determine the effect of work discipline on employee performance in state-owned hospitals in Medan. To determine the effect of training on employee performance at government-owned hospitals in Medan. To determine the effect of organizational culture on employee performance in government-owned hospitals in Medan. To determine the effect of organizational culture moderating work discipline on employee performance in government-owned hospitals in Medan. To determine the effect of organizational culture moderating training on employee performance in government-owned hospitals in Medan. In this study the object of study was permanent employees at a government-owned hospital in Medan with a sample of 75 people. The study in this case conducted a sampling technique because the total population was used as the number of samples so this study was a sample study. Data collection techniques in this study is to use a questionnaire (Questionnaire). While the data analysis technique used is to test classical assumptions, multiple linear regression, hypothesis, coefficient of determination and moderation.